Cambodia : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
Cambodia's 2004 Article IV Consultation reports that the macroeconomic performance has been generally good, reflecting both favorable external developments and prudent fiscal policy. Exports soared following a bilateral trade agreement with the United States, and large aid inflows helped finance domestic investment and spurred construction activities. Prudent fiscal policy has been the key to ensuring price stability. Overall GDP growth has been robust mainly because of a strong rebound in agricultural production.